A Wandering Abdominal Mass in a Neonate: An Enteric Duplication Cyst Mimicking an Ovarian Cyst - Shigeo Iijima (Case Reports in Pediatrics)
Enteric duplication cysts are rare congenital anomalies that are prenatally diagnosed through antenatal ultrasonography (US). In female patients, however, attention must be paid since these formations might be confused with ovarian cysts. Herein, we present a case of a low birth weight female infant with an enteric duplication cyst. A cystic lesion was detected in the right abdomen of the fetus on antenatal US and magnetic resonance imaging (MRI). Serial US and MRI examinations performed after birth showed a single cyst that wandered from side to side in the abdomen; the initial diagnosis was thought to be an ovarian cyst. During laparotomy, however, it was found to be an enteric duplication cyst with volvulus. To our knowledge, there has been no report of an enteric duplication cyst presenting as a wandering abdominal mass. Our experience indicates that early intervention is necessary for patients who have a wandering abdominal mass to avoid complications and urgent surgery, whether it is an ovarian cyst or an enteric duplication cyst.